2016
DOI: 10.3389/fmars.2016.00064
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Validation of a Habitat Suitability Index for Oyster Restoration

Abstract: Habitat suitability index (HSI) models provide spatially explicit information on the capacity of a given habitat to support a species of interest, and their prevalence has increased dramatically in recent years. Despite caution that the reliability of HSIs must be validated using independent, quantitative data, most HSIs intended to inform terrestrial and marine species management remain unvalidated. Furthermore, of the eight HSI models developed for eastern oyster (Crassostrea virginica) restoration and fishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…To determine the form of the relationship between HSI and normalized oyster density, we used a global curve fitting program (Systat, 2007) to fit linear, exponential, quadratic and sigmoid functions to the relationships based on functions selected in previous HSI studies (Soniat and Brody, 1988;Reiley et al, 2014;Theuerkauf and Lipcius, 2016). Akaike Information Criterion (second-order bias correction estimator, AICc) was used to verify the best fitting model of the four possible functions.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the form of the relationship between HSI and normalized oyster density, we used a global curve fitting program (Systat, 2007) to fit linear, exponential, quadratic and sigmoid functions to the relationships based on functions selected in previous HSI studies (Soniat and Brody, 1988;Reiley et al, 2014;Theuerkauf and Lipcius, 2016). Akaike Information Criterion (second-order bias correction estimator, AICc) was used to verify the best fitting model of the four possible functions.…”
Section: Model Validationmentioning
confidence: 99%
“…Substantial changes to estuarine ecosystems over time may preclude the usefulness of historical records for present-day site selection (Jackson et al, 2001). More recently, HSI models have been developed to inform the oyster restoration site selection process (Soniat and Brody, 1988;Mann and Evans, 2004;Barnes et al, 2007;Starke et al, 2011;Beseres Pollack et al, 2012;Linhoss et al, 2016; Theuerkauf and Lipcius, 2016). These models have included many factors relevant to oyster biology and subsidence of artificial reefs, such as salinity and sediment type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study sites were chosen based on standard restoration site criteria: water depth < 3 m, sand to muddy-sand bottom, and close proximity to oyster broodstock (Woods et al 2004, Theuerkauf & Lipcius 2016. Sites within rivers represented a range of energetic conditions, as characterized by their geographic location, fetch, and sediment type, with one highenergy (GWR1, LR2) and one low-energy (GWR2, LR1) site in each river.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Recent studies have identified oyster reef geometry, particularly height above the seabed, as an important factor driving restoration success, presumably due to positive feedbacks between reef structure, hydrodynamics and resulting population dynamics (Lenihan 1999, Powers et al 2009, Schulte et al 2009, Theuerkauf & Lipcius 2016. Lenihan (1999) determined that oyster growth and survival was highest on crests of reefs >1.0 m while sedimentation and mortality was highest at the base of reefs and on short reefs (0.1 m).…”
Section: Introductionmentioning
confidence: 99%